Pengembangan Media 3 Lagu Pendek Tokoh Pewayangan dalam Muatan Lokal Mata Pelajaran Bahasa Jawa - Veronica Titilaras Widyasari; Elvira Hoesein Radia (Jurnal Bidang Pendidikan Dasar, 2022)
This research aims to determine the media feasibility of 3 short songs about wayang characters for a local content Bahasa Jawa lesson and know the students’ interest in the media. This type of research is R&D based on Borg & Gall procedure modified by Sukmadinata (2016). The analysis data research and data student responses used descriptive technique percentage and categories. The products tested by the media expert, content expert, and language expert to know the feasibility of the media. The results of the test from media expert got 89,5% or very feasible, from the content expert got 91,6% or very feasible, from language expert got 90% or very feasible. The results of the test showed that the media are worthy to apply for the elementary students then the writers did the research to know the students’ interest in media and got 92,5% media are very interesting